2008
DOI: 10.1016/j.dsr.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Drift pumice in the Central Indian Ocean Basin: Geochemical evidence

Abstract: Abundant white to light grey coloured pumice without ferromanganese oxide coating occurs within the Quaternary sediments of the Central Indian Ocean Basin. Two distinct groups of pumice are identified from their geochemical composition, which allow one to define two different origins linked to two separate eruptions. One group of pumice is a dacitic type characterized by high Fe, Ti, Mg, Al and Ca with comparatively low contents of Si, rare earth elements (Σ REE-69 ppm), Rb, Sr, U, Th, Ba, V, Nb, Sc, Mo and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…These pumices are mostly rounded to sub-rounded, similar to the earlier observations of Pattan et al (2008) which indicates their long transportation and abrasion. Iyer and Karisiddaiah (1988) studied 48 pumices and more recently, Kalangutkar et al (2011) analysed about 400 pumice clasts from CIOB and found that majority of them are equant and oblate Zingg shapes.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…These pumices are mostly rounded to sub-rounded, similar to the earlier observations of Pattan et al (2008) which indicates their long transportation and abrasion. Iyer and Karisiddaiah (1988) studied 48 pumices and more recently, Kalangutkar et al (2011) analysed about 400 pumice clasts from CIOB and found that majority of them are equant and oblate Zingg shapes.…”
Section: Discussionsupporting
confidence: 76%
“…The REE content of these pumice grains is very similar to each other and as well as that of the uncoated pumice from the CIOB (121 ppm, Pattan et al, 2008), These P REE contents and profiles are similar to material from the Toba Caldera; to glass shards of YTT origin from different locations such as the CIOB, Peninsular India, South China Sea, Arabian Sea; and to Layers A, C and E from ODP-758 (Westgate et al, 1998;Song et al, 2000;Pattan et al, 2001Pattan et al, , 2002). An ash layer was described from ODP 758 at w8.2 Ma (Late Miocene) which also has similar REE concentrations ( P REE 123 ppm) to the coated pumices, and this has been speculated to be of Toba origin (Padmakumari and Ahmad, 2004).…”
Section: Oxidesmentioning
confidence: 72%
See 3 more Smart Citations